Professorial Lecture by Prof Ir. Dr. Norlida Buniyamin: engineering education & practice in Malaysia - Buniyamin, Norlida (2022)
Full transcript of the Majlis Syarahan Profesor by YBhg. Prof. Ir. Dr. Norlida Buniyamin entitled “Engineering Education Transformation: Navigating Challenges and Inspiring Change” held at Universiti Teknologi MARA (UiTM). Includes the complete text of the ceremony, speaker introduction, and lecture content focusing on the transformation of engineering education, innovation in teaching and learning, and the role of leadership in driving academic excellence and institutional development.